2021
DOI: 10.1093/eurheartj/ehab724.2675
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary exercise test in patients with persistent dyspnea after COVID-19 disease

Abstract: Introduction Persistent dyspnea in patients who have suffered from COVID-19 disease has become a constant in cardiology in recent months. Healther workers have been one of the population groups mainly affected during the pandemic. Chronic involvement by COVID-19 infection, such as dyspnea, is frequent, and so far, of unknown mechanism. CardioPulmonary Exercise Test (CPET) is currently the gold standard technique in the differential diagnosis of dyspnea. Therefore, CPET could be useful in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
0
8
1
Order By: Relevance
“…Deconditioning is commonly reported, perhaps because most studies predominantly included hospitalized individuals and even non-hospitalized individuals experience deconditioning after illness. 22,[80][81][82][83][84] Although we observed findings consistent with deconditioning or obesity in a few individuals (earlier anaerobic threshold, accelerated heart rate response), our findings argue against deconditioning as the primary explanation. Identifying deconditioning as a cause is challenging because it is also an effect of reduced habitual exercise among symptomatic individuals.…”
Section: Other Studies Of Pasc Using Cpetcontrasting
confidence: 53%
See 1 more Smart Citation
“…Deconditioning is commonly reported, perhaps because most studies predominantly included hospitalized individuals and even non-hospitalized individuals experience deconditioning after illness. 22,[80][81][82][83][84] Although we observed findings consistent with deconditioning or obesity in a few individuals (earlier anaerobic threshold, accelerated heart rate response), our findings argue against deconditioning as the primary explanation. Identifying deconditioning as a cause is challenging because it is also an effect of reduced habitual exercise among symptomatic individuals.…”
Section: Other Studies Of Pasc Using Cpetcontrasting
confidence: 53%
“…Multiple case series have reported that deconditioning is the primary cause of exercise limitation in PASC. 20,[69][70][71][72] Our findings argue against deconditioning as the primary explanation as the Durstenfeld et al CPET, CMR, and Ambulatory Rhythm Findings >12 months after COVID-19 majority of individuals had normal oxygen pulse and normal VO2 to work slope which suggest normal augmentation of cardiac output. We found earlier anaerobic thresholds which can be seen in deconditioning and identified three individuals (8% of sample, 20% with reduced exercise capacity) whose pattern of findings is most consistent with deconditioning, obesity, or alterations in peripheral oxygen utilization.…”
Section: Role Of Deconditioning In Pascmentioning
confidence: 54%
“…We identified 1 interventional study of cardiac rehabilitation 67 with baseline CPET reported in an included study. 68 27,30,33,35,36,44,47,49,52,55,56,62,66,68 only included individuals who were hospitalized for acute infection (median, 70% [range, 0-100%] hospitalized), and 15 studies (39.5%) 30,32,[39][40][41][42][43]50,51,54,55,57,59,61,64 included individuals with prevalent symptoms at CPET (median, 95% [range, 38%-100%] symptomatic).…”
Section: Resultsmentioning
confidence: 99%
“…Deconditioning was reported as the most prevalent pattern by 10 studies, 27,33,35,36,46,59,[61][62][63][64] with alterations in muscular oxygen utilization acknowledged as an alternative explanation by some.…”
Section: Patterns Of Reduced Exercise Capacitymentioning
confidence: 99%
“…Deconditioning was the most commonly identified pattern and the main cause of reduced exercise capacity reported by 8 studies. 39,40,42,[46][47][48][49][50][51] Although ventilatory limitations were uncommon, multiple studies reported dysfunctional breathing or hyperventilation. 50,[52][53][54][55][56][57] Muscular/peripheral oxygen extraction abnormalities were also commonly reported.…”
Section: Patterns Of Reduced Exercise Capacitymentioning
confidence: 99%